Nursing Challenges in Motivating Nursing Students through Clinical Education: A Grounded Theory Study - Hanifi Nasrin; Parvizy Soroor; Joolaee Soodabeh (Nursing Research and Practice)
Nurses are the first role models for students in clinical settings. They can have a significant role on students’ motivation. The purpose of this study was to explore the understanding of nursing students and instructors concerning the role of nurses in motivating nursing students through clinical education. The sampling was first started purposefully and continued with theoretical sampling. The study collected qualitative data through semistructured and interactive interviews with 16 nursing students and 4 nursing instructors. All interviews were recorded, transcribed, and analyzed using grounded theory approach. One important pattern emerged in this study was the “concerns of becoming a nurse,” which itself consisted of three categories: “nurses clinical competency,” “nurses as full-scale mirror of the future,” and “Monitoring and modeling through clinical education” (as the core variable). The findings showed that the nurses’ manners of performance as well as the profession’s prospect have a fundamental role in the process of formation of motivation through clinical education. Students find an insight into the nursing profession by substituting themselves in the place of a nurse, and as result, are or are not motivated towards the clinical education.